Network protocols for security professionals : probe and identify network-based vulnerabilities and safeguard against network protocol breaches /: probe and identify network-based vulnerabilities and safeguard against network protocol breaches. (2022) - Orzach, Yoram; Khanna, Deepanshu
No abstract available